PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL MENURUT UNDANG – UNDANG NO.23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - novy septia dewi (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACT With the issuance of Law No.23 of 2002 on Child Protection Child Protection is mentioned understanding of all activities to ensure and protect children and their rights in order to live , grow, develop and participate optimally in accordance with the dignity of humanity , and got protection from violence and discrimination . The use of the term sexual harassment in the title has a broad meaning that sexual harassment has a broad meaning , namely of activities that are assumed to lead to sexual harassment , such as touching or groping body parts that are sensitive or vital . And the authors provide restrictions on the problem of sexual intercourse that occurred against minors committed by an adult . Fit the real conditions that exist that the implementation of the legal protection of children has been conducted by law enforcement authorities to request the testimony of the victim who was accompanied by parents and agencies engaged in the field of women and children Based on the results of the study authors in Samarinda Police and Child Protection Agency ( LPA ) Samarinda child protection is based on the data and information it can be concluded that the authors expected that law enforcement authorities , lembag - related institutions , families and communities can continue to work together to provide care and legal protection to victims of sexual abuse as a support to avoid the trauma of harassment in the future so that this nation has a better generation Keywords: child protection, sexual harassment